Ambientes de aprendizaje en el proceso de enseñanza aprendizaje de la asignatura de Física en el Bachillerato General Unificado de la Unidad Educativa Fiscomisional “Daniel Álvarez Burneo” - González Ordoñez, Ana Cristina (2023)
The purpose of this research is to analyze the importance of learning environments in the Physics teaching-learning process, at Daniel Alvarez Burneo school. The study followed a mixed approach, exploratory and descriptive, based on documentary and field research. The collection of information was carried out through the application of observation sheets and interviews with teachers. complemented with the documentary review on the study categories. As a main result, it was determined that teachers use the designs of learning environments focused on knowledge and on the learner with a traditional spatial organization, therefore, the interaction between students during the educational act is not adequate. It is concluded that a well-organized, safe and stimulating learning environment facilitates the teaching-learning process of Physics. Keywords: spatial organization, environment designs, learning environments, Physics